Creation of theoretical road traffic noise model with the help of GIS - Szopińska, Kinga (International Conference “Environmental Engineering”, 2017)
Road traffic noise, as a form of environmental pollution, is an important element causing discomfort among inhabitants and leading to the emergence of noise nuisance influencing the shaping of urban space. The basic tool in combating noise is a Strategic Noise Map (SNM), which, understood as a system, constitutes an element of a city’s information layer. The system, illustrating the noise situation within a city, is prepared by means of a calculation measurement method using specialized computer programs. The assessment of road traffic noise begins by defining the amount of noise emissions coming from acoustically-homogenous sections (emission map), and ends with determining the extent of noise propagation in urban space (immission map). The above process is based on the analysis of actual input data describing, in a detailed manner, the analyzed road infrastructure in terms of the characteristics of the road section, information on the volume and type of traffic, and data on the organization of traffic. Under such extensive analysis of the condition of the environment, it is appropriate to apply GIS data as a methodological basis for creating SNMs. GIS data make it possible to unify the rules for collecting and archiving values characterizing the condition of the environment, as well as parameters influencing the level of noise. The aim of work is create a theoretical road traffic noise model with the help of GIS. The scope of information in attribute tables of acoustically-homogenous road sections comprising a GIS thematic layer was described in detail. The above information are the basis for generating digital road traffic noise emission maps as well as being the starting point for assessing road traffic noise in the area of a city in the form of immission maps. The article additionally analyzes the results of data derived from the first phase of noise mapping in Europe, as well as familiarizing the reader with the procedure of modelling road traffic noise emission in accordance with the CNOSSOSEU which will become binding as of 31 December 2018 throughout the European Union, and which was introduced by the provisions of the new noise directive – Directive 2015/996 of 19 May 2015.
Keywords: emission; road traffic noise; CNOSSOS-EU; strategic noise map (SNM); GIS; Poland